2016
DOI: 10.1037/xlm0000285
|View full text |Cite
|
Sign up to set email alerts
|

An eye-tracking investigation of written sarcasm comprehension: The roles of familiarity and context.

Abstract: This article addresses a current theoretical debate between the standard pragmatic model, the graded salience hypothesis, and the implicit display theory, by investigating the roles of the context and of the properties of the sarcastic utterance itself in the comprehension of a sarcastic remark. Two eye-tracking experiments were conducted where we manipulated the speaker’s expectation in the context and the familiarity of the sarcastic remark. The results of the first eye-tracking study showed that literal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 35 publications
8
25
1
Order By: Relevance
“…We replicated the previous findings that sarcastic utterances are more likely to attract look-backs and that readers tend to initiate more look-backs to other parts of text from sarcastic than from literal utterances (Au-Yeung et al, 2015;Filik et al, 2014;Filik & Moxey, 2010;Kaakinen et al, 2014;Olkoniemi et al, 2016;Olkoniemi et al, in press;Turcan & Filik, 2016). In the beginning of the experiment, sarcastic utterances also received longer look-backs from the spillover region, implying increased sentence wrap-up processing (Rayner et al, 2000).…”
Section: Processing Of Sarcasm and Sarcasm Comprehensionsupporting
confidence: 86%
See 1 more Smart Citation
“…We replicated the previous findings that sarcastic utterances are more likely to attract look-backs and that readers tend to initiate more look-backs to other parts of text from sarcastic than from literal utterances (Au-Yeung et al, 2015;Filik et al, 2014;Filik & Moxey, 2010;Kaakinen et al, 2014;Olkoniemi et al, 2016;Olkoniemi et al, in press;Turcan & Filik, 2016). In the beginning of the experiment, sarcastic utterances also received longer look-backs from the spillover region, implying increased sentence wrap-up processing (Rayner et al, 2000).…”
Section: Processing Of Sarcasm and Sarcasm Comprehensionsupporting
confidence: 86%
“…In this type of setting, a reader must search for an alternative interpretation of the utterance and incorporate this into the memory representation of the text. In support of these theoretical views, recent eye-tracking studies have shown that written sarcastic utterances take more time to process and are harder to comprehend than their literal counterparts (Au-Yeung, Kaakinen, Liversedge, & Benson, 2015;Filik, Leuthold, Wallington, & Page, 2014;Filik & Moxey, 2010;Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014;Olkoniemi, Ranta, & Kaakinen, 2016;Olkoniemi, Strömberg, & Kaakinen, in press;Turcan & Filik, 2016).…”
Section: Resolving the Meaning Of Sarcastic Utterancesmentioning
confidence: 94%
“…The above‐mentioned theoretical proposals have been operationalized and translated into experimental predictions that are focused on the temporal dimension of irony interpretation (i.e., when literal and ironic interpretations become available). Behavioral evidence supporting classic modular models showed that the ironic interpretation requires more time and processing costs as compared to the literal/salient interpretation (Dews & Winner, ; Fein, Yeari, & Giora, ; Filik & Moxey, ; Giora et al., ; and Turcan & Filik, for unfamiliar ironic phrases). On the other hand, behavioral findings supporting interactive models showed that, with a facilitating context (usually describing negative events and triggering ironic criticism), the ironic meaning can become available as fast as the literal interpretation (Gibbs, ; Ivanko & Pexman, ).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, some researchers have examined the online processes underlying sarcasm comprehension using eye-tracking (e.g. Au-Yeung, Kaakinen, Liversedge, & Benson, 2018;Deliens, Antoniou, Clin, Ostashchenko, & Kissine, 2018;Filik, Howman, Ralph-Nearman, & Giora, 2018;Filik, Leuthold, Wallington, & Page, 2014;Filik, & Moxey, 2010;Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014;Olkoniemi, Ranta, & Kaakinen, 2016;Olkoniemi, Johander, & Kaakinen, 2019;Olkoniemi, Strömberg, & Kaakinen, 2019;Țurcan & Filik, 2016;. These studies generally find that comprehending irony incurs higher processing costs than comprehending literal language, suggesting that the salient meaning (i.e.…”
Section: Emotional Processing Of Ironic Vs Literal Criticism In Autimentioning
confidence: 99%